ISLAMIC LAW PHILANTHROPY IN INSTITUTIONS AND URBAN VILLAGE COMMUNITY EMPOWERMENT PATTERNS IN PAREPARE CITY - Hannani,; Hasim, Hasanuddin; Abdillah, (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2023)
Parepare city community empowerment through Parepare Mayor Regulation No. 4 of 2019 concerning Guidelines for Community Empowerment Institutions for the City of Parepare Village is a step by the city government in increasing the empowerment of the keluran community, but it is inversely proportional to the poverty rate from 2019-2022 which has shown a drastic increase, this is what makes researchers want to see the implementation of the mayor's regulations and community empowerment parepare city from an Islamic philanthropic perspective, this research method is a qualitative research using library research and field research methods, Islamic philanthropy and the concept of the Indonesian state are manifested linearly with Parepare Mayor Regulation No.4 of 2019 concerning guidelines for implementing village community empowerment institutions including namely : 1) Facilitate the municipal government of Parepare in preparing and implementing policies that are aspirational and right on target or needed by the community; and 2) Management of LPMK is more structured and systematic. However, the problem with the implementation of these rules lies in human resources, communication and socialization and the massive management of LPMK in Parepare City.